The Level of Understanding of Grade X Students of SMA N 1 Maos Cilacap on Physical Fitness - Kusmiyati Kusmiyati; Dian Imam Saefulah; Miftahul Hidayat (International Journal of Science and Applied Science: Conference Series, 2022)
Physical fitness is one of the subjects that must be given to students. However, not all students are able to accept as a whole about the material given by the teacher. The purpose of this study was to determine the level of understanding of grade X students of SMA N 1 Maos Cilacap towards physical fitness. This research is a quantitative descriptive research with survey method. The study population was all grade X students of of SMA N 1 Maos Cilacap totaling 648 students. The research sample was taken by 38% of the population of 247 students determined using the Slovin formula. Sample determination using cluster random sampling technique. The instrument uses a test in the form of a previous questionnaire in the form of a google form that has been tested for validity by experts and the reliability results can be received with a value of 0.76. The content of this instrument contains 38 points of true-false statements. The analysis technique used is descriptive statistics with the help of Microsoft Excel. Then the analysis data obtained are presented in frequency tables and categorized. The results of this study showed that the level of understanding of physical fitness was 5.26% included in the "Very Good" category, 22.27% was included in the "Good" category, 48.99% was included in the "Sufficient" category, 16.60% was included in the "Less" category, and 6.88% was included in the "Poor" category. So it can be concluded that the level of understanding of physical fitness is mostly included in the "Enough" category.